The impact of 45S5-bioactive glass on synovial cells in knee osteoarthritis: an in vitro study - Platzer, Hadrian; Marinescu, Max; Nawaz, Qaisar; Tripel, Elena; Gantz, Simone; Horsch, Axel; Daniel, Volker; Boccaccini, Aldo R.; Hagmann, Sébastien; Moradi, Babak; Renkawitz, Tobias; Westhauser, Fabian (Materials, 2023)
Synovial inflammation in osteoarthritis (OA) is characterized by the release of cartilage-degrading enzymes and inflammatory cytokines. 45S5-bioactive glass (45S5-BG) can modulate inflammation processes; however, its influence on OA-associated inflammation has hardly been investigated. In this study, the effects of 45S5-BG on the release of cartilage-degrading metalloproteinases and cytokines from synovial membrane cells (SM) isolated from patients with knee OA was assessed in vitro. SM were cultivated as SM monocultures in the presence or absence of 45S5-BG. On day 1 (d1) and d7 (d7), the concentrations of Matrix Metalloproteinases (MMPs) and cytokines were assessed. In 45S5-BG-treated SM cultures, MMP9 concentration was significantly reduced at d1 and d7, whilst MMP13 was significantly increased at d7. Concentrations of interleukin (IL)-1B and C-C motif chemokine ligand 2 (CCL2) in 45S5-BG-treated SM cultures were significantly increased at both time points, as were interferon gamma (IFNG) and IL-6 at d7. Our data show an effect of 45S5-BG on SM activity, which was not clearly protective, anti-inflammatory, or pro-inflammatory. The influence of 45S5-BG on MMP release was more suggestive of a cartilage protective effect, but 45S5-BG also increased the release of pro-inflammatory cytokines. Further studies are needed to analyze the effect of BGs on OA inflammation, including the anti-inflammatory modification of BG compositions.